The Effect of Good Corporate Governance and Employee Loyalty on Employee Performance on Hajj and Umrah Travel at PT Panglima Ekspres Surabaya - Fivi Linda Sari; Airlangga Bramayudha (Proceedings of International Conference on Da'wa and Communication, 2019)
The purpose of this study was to determine the effect of good corporate governance programs and employee loyalty on employee performance partially or simultaneously at PT. Panglima Express Surabaya. The method used in this research is quantitative research, the type of associative hypothesis. The method used by researchers in answering these objectives is by using multiple linear regression tests. This research is located at PT. Panglima Express Surabaya with a total of 30 respondents. The results of this study indicate that (1) The influence of good corporate governance and employee loyalty on employee performance at PT. Panglima Express Surabaya partially (a) the value of good corporate governance has a p-value of 0.000 <0.05 (b) the value of employee loyalty has a p value of 0.000 <0.05, (2) The significant value of good corporate governance (X1), employee loyalty ( X2) on employee performance (Y) has a significant effect with the p value is 0.000 <0.05, (3) The value of the relationship between good corporate governance and employee loyalty to employee performance at PT. Panglima Ekspres Surabaya partially (a) The correlation value of good corporate governance with employee performance is 0.624 (b) The correlation value between employee loyalty and employee performance is 0.808, (4) The value of the relationship can be seen from the value in column R. The value in column R can be It is known that the variable good corporate governance X1 and employee loyalty X2 has a relationship value to employee Y performance of 0.815, (5) The value of "Standard Error of the Estimate (SEE)" is 3.44135, Descriptive statistic, namely 5.72592, The correlation value for good corporate governance is 0.624. The employee loyalty value is 0.808. This shows that the strongest or dominant relationship value is the employee loyalty variable, because the employee loyalty variable has the highest relationship value, namely 0.808.